Needs Assessment for Developing Digital Learning Media in Chemistry for Grade XI Students at SMA Negeri 2 Siak Hulu - Wulandari, Manja Septi; hidayati, Nurkhairo; Rahmayulis, Putri Ade (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
This study aims to analyse the needs for developing digital-based learning media for teaching chemistry in Grade XI of senior high school. The research was conducted at SMA Negeri 2 Siak Hulu in January 2025. Data collection techniques included questionnaires and interviews. The questionnaire data were collected using the Likert scale, while the interview data were analysed descriptively. This research employed a mixed-methods approach, combining qualitative and quantitative methods, with a phenomenological perspective using Interpretative Phenomenological Analysis (IPA). The results showed that the need for digital-based learning media at SMA Negeri 2 Siak Hulu reached 75%, categorised as "moderately needed." Furthermore, the interview findings supported the quantitative data, revealing that the school requires digital learning media development. Therefore, this study concludes that it is necessary to develop digital-based learning media to support the chemistry learning process for Grade XI students to enhance teaching effectiveness and student engagement.